An assessment of barriers to uptake of hiv counselling and testing among out-of-school youth in Ebonyi state, Nigeria (2020)
HIV counselling and testing (HCT) is the entry point to HIV care and supports. There are still major research gaps regarding why there is low uptake of HCT among out-of-school youths. This study examined the barriers to HCT among out-of-school youths in Ebonyi state, Nigeria. Seventy out-of-school youths with age range of 15-24 years and mean years of 18.5 years purposely drawn from artisans in Ebonyi state participated in the study. Three sessions of FGD were held with the 2 age categories (15-18 & 19 - 24 years). In addition to note taking, all the sessions were audio-recorded and transcribed. Content analysis was done and the following themes emerged: (1) dominant barrier to HCT was fear associated with HCT results and stigma. Other barriers include: (2) low level of HIV knowledge, (3) low risk perception and (4) ignorance of HCT location in Ebonyi State. It concluded that there are individual and social factors which act as barriers to out-of-school youths to seek HIV testing in Ebonyi State. To increase youth utilization of HCT service, there is a need to address these barriers when developing a model for out-of-school youths.